Marketing of Batik Based on Consumer Preferences - Indah Wahyu Utami; Adcharina Pratiwi; Ilham Sentosa (LPPM Universitas Duta Bangsa Surakarta, 2019)
The purpose of this study was to determine consumer preferences about batik products and the effect of 4P (product, price, promotion, place) on marketing performance. The benefits of this research are known batik products that are preferred by consumers and the magnitude of the influence of 4P variables on marketing performance. Methods of data collection through direct observation, questionnaires, literature study and interviews, documentation of field research. The samples in this study were 10 batik entrepreneurs and 100 consumers who bought batik at the Masaran batik industry center. Data analysis methods through conjoint analysis to determine consumer preferences about batik and regression analysis to determine the relationship and influence of 4P on marketing performance. The results of this study are (a) performance: batik appears moderate and inconspicuous; traditional patterned/patterned features; washed not faded; motifs such as batik on the market; last 3-5 years; batik; soft color combination; have a brand; not made by a well-known businessman; enough quality and affordable prices. While the price (b) the price is below Rp. 50.000/picis; cash payment system; buy more than 3 picis get a discount; cheaper prices on the market. For promotion (c) making audio-visual advertisements on television/radio so they are more widely known by the public; sold using marketing personnel; no need to follow the event; no need to do CSR; the target of advertising is widely known by the people of Central Java. For distribution: (d) batik does not have to be sold in every shop in all regencies/cities in Indonesia; delivery of goods to the customer's address must be faster than promised; batik products are also sold through online stores; n batik products are sold in stores/outlets in Sragen and surrounding areas. The dominant variable influencing marketing performance is product, then price, distribution and promotion.